Greenhouse gases emissions in rivers of the Tibetan Plateau. Issue 1 (December 2017) - Qu, Bin; Aho, Kelly; Li, Chaoliu; Kang, Shichang; Sillanpää, Mika; Yan, Fangping; Raymond, Peter
Abstract Greenhouse gases (GHGs) emissions from streams are important to regional biogeochemical budgets. This study is one of the first to incorporate stream GHGs (CO2, CH4 and N2 O) concentrations and emissions in rivers of the Tibetan Plateau. With one-time sampling from 32 sites in rivers of the plateau, we found that most of the rivers were supersaturated with CO2, CH4 and N2 O during the study period. Medians of partial pressures of CO2 (pCO2 ), pCH4 and pN2 O were presented 864 μatm, 6.3 μatm, and 0.25 μatm respectively. Based on a scaling model of the flux of gas, the calculated fluxes of CO2, CH4 and N2 O (3, 452 mg-C m2 d−1, 26.7 mg-C m2 d−1 and 0.18 mg-N m2 d−1, respectively) in rivers of the Tibetan Plateau were found comparable with most other rivers in the world; and it was revealed that the evasion rates of CO2 and CH4 in tributaries of the rivers of the plateau were higher than those in the mainstream despite its high altitude. Furthermore, concentrations of GHGs in the studied rivers were related to dissolved carbon and nitrogen, indicating that riverine dissolved components could be used to scale GHGs envision in rivers of the Tibetan Plateau.